Android Application Development for Secure Data Transmission using Steganography - Jeswani, Vineet Ramesh; Kulkarni, Savita; Ingle, Manisha (Discoveries in Agriculture and Food Sciences, 2015)
Real time implementation of Steganographic algorithm along with encryption is used to achieve secure data flow across Android mobiles. In this paper, pixel value differencing (PVD) technique one of the steganographic algorithm with AES encryption are implemented using JAVATM on android platform to achieve high level security for real time multimedia messaging service (MMS) system. One of the important concerns in any communication system is the security of the data transmission from eavesdropper. To overcome this security problem, the most effective technique is the steganography. Steganography is used to hide secret information onside some carrier. Image is taken as a carrier file to hide secret information (text, image, audio). To add more security, encryption is also done on the secret file which will be hidden inside MMS. The Pixel Value Differencing (PVD) technique is used to hide secret information (text, image, audio). Different sizes of secret images are considered keeping the fixed size of cover image and the calculations have been done for MSE and PSNR of image in MATLAB. Later, the results of the PVD are compared with the LSB technique. Encryption and Steganographic algorithms are ported on Sony Xperia M mobile device with Android version 4.3. Keywords – Android Platform, Encryption, LSB, PVD, MMS, MSE, PSNR, Security, Steganography.